The Coconut Industry: A Review of Price Forecasting Modelling in Major Coconut Producing Countries - Abeysekara, M. G. D.; Waidyarathne, K.P (International Coconut Community Journal, 2020)
The global supply and demand of coconuts and coconut-based products have been increased tremendously over the past decades; hence, the industry has become one of the significant contributors to the economies of producer countries. However, similar to the other agricultural industries, coconut has confronted by fluctuation in prices and accords the importance of reliable price modelling and forecasting techniques to ease the burden on the value chain actors. Therefore, the objective of this paper is to review the main approaches used in modelling and forecasting coconut prices, with an assessment of the strengths and weaknesses of each approach. The modelling techniques used in coconut price forecasting were mainly time series models dominated by univariate time series models. This type of models excessively confines the analysis to a single variable, despite the many interactions affected in a system of coconut pricing. The major drawback in existing price modelling studies is the absence of interacting factors such as prices, production, climatic variables and their interactions as a system. Therefore, it is important to extend the existing studies of coconut price modelling and forecasting with a system’s approach by including other influencing variables to generate more realistic forecast values, allowing the industry to adopt its changing circumstances. Keywords: Coconut, modelling, price forecasting, time series models, system’s approach